Adolescents who perceive fewer consequences of risk‐taking choose to switch off games later at night. (13th March 2015) - Reynolds, Chelsea M.; Gradisar, Michael; Kar, Kellyann; Perry, Ashleigh; Wolfe, Jasper; Short, Michelle A.
Abstract Aim Technology use by adolescents close to bedtime commonly leads to sleep problems, and individual factors predicting those at heightened risk are under studied. We investigated whether risk‐taking perceptions influenced length of adolescent technology use at bedtime and whether being aware of time moderated this association. Methods We recruited 16 males and five females, with a mean age of 17.6 years, from school and university populations to assess adolescent technology use and bedtimes. They were assessed for trait risk‐taking using the Cognitive Appraisal of Risky Events questionnaire and had unrestrained access to a video game on two separate nights, counterbalanced for clock present or clock absent conditions. The adolescents' self‐selected bedtime provided a measure of the level of technology use and was the dependent variable. Results Adolescents who perceived fewer negative consequences of risky activities on the Cognitive Appraisal of Risky Events played the video game longer and went to bed later than those who perceived more negative consequences (p = 0.03). There was no influence on bedtimes from perceived benefits of risk‐taking or clock presence. Conclusion Adolescents who perceived fewer negative consequences of risk‐taking were more likely to stay up later using technology, facing a heightened risk of displaced sleep.